Numerical Analysis of Deep Excavation (University of Khartoum Engineering Journal, 2022)
Because of limited knowledge on experience on deep excavation analysis in Sudan, this study aimed to study numerical models for modeling deep excavation and adjacent buildings or public facilities near by the excavation. A series of parametric studies were conducted to evaluate the effect of wall stiffness and strut stiffness. The numerical analysis results showed that the increase of retaining wall stiffness or strut stiffness to reduce wall deformation is certainly effective, however does not have linear relationship. Last, based on the numerical results, the evaluation of adjacent building damage related to settlement induced by excavation and suggestions protection of adjacent buildings before and during excavation were discussed.